Minding the gap - Halpern, Nathan ca. 20. Jh; Ruggiero, Chris (<<The>> Criterion Collection, 2021)
"This extraordinary debut from documentarian Bing Liu weaves a story of skateboarding, friendship, and fathers and sons into a coming-of-age journey of courageous vulnerability. Over the course of several years and with his camera always at the ready, Liu records the rocky paths into adulthood of Keire and Zack, two friends from his own skateboarding community in Rockford, Illinois. As he does so, deeper parallels emerge that ultimately draw the filmmaker into a heartrending confrontation with his own past. With images of exhilarating poetry and a keen emotional sensitivity, Minding the Gap is a powerfully cathartic portrait of fledgling lives forged in trauma and fighting to break free." [criterion.com]
Original: USA 2018
director-approved DVD special edition features: new high-definition digital master, approved by director Bing Liu ; two new audio commentaries, one featuring Liu and the other featuring Liu and documentary subjects Keire Johnson and Zack Mulligan ; new follow-up conversation between Liu and documenatry subject Nina Bowgren ; new programs featuring interviews with professional skateboarder Tony Hawk and with Liu, executive producer Gordon Quinn, and producer Diane Quon ; four outtake scenes with introductions by Liu ; "Nước (2010), a short film by Liu about two Vietnamese immigrants growing up American ; trailer ; English subtitles for the deaf and hard of hearing ; plus: an essay by critic Jay Caspian Kang
Bildformat 1.78:1
Keywords: Skateboarder; Alltag; Männliche Jugend; Rockford, Ill.; Film; DVD-Video